The rebirth of the Lebanese identity in the philosophy of the Lebanese intellectual Samir Kassir - Cohen, Ronen A. (Cogent social sciences, 2017)
During the last years of the Syrian control of Lebanon, Samir Kassir was undoubtedly one of the prominent Lebanese journalists who fought against it and tried to more distinctly define the fragile and broken Lebanese nationality. Kassir was mainly active in political comment and analysis and tried to introduce new and fresh ideas in order to awaken the Lebanese people from their ongoing lack of political consciousness, coma and social degeneration. He tried to bring about a shift in political views that originated in the people, Lebanon’s grass roots, rather than try to change the elite and corrupt political framework. His political and intellectual activities offered the Lebanese a new and promising national agenda that, supported by other similarly concerned intellectuals, might have given the Lebanese new hope in their turmoil. The article examines Kassir’s part in building the new hybrid Lebanese identity and argues that Kassir, as a modern Lebanese intellectual, first diagnosed the core problems involved in creating this Lebanese identity and later suggested his own understanding of what such a hybrid, reconstructed identity should be.